hw4_soln_rough - w ( x, t ) gives w t ( x, t )-kw xx ( x, t...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Problems from 2.4 of Strauss: 16. Set v ( x, t ) = e bt u ( x, t ). By computation, if u ( x, t ) solves the heat equation with constant dissipation and initial data u ( x, 0) = φ ( x ), then v ( x, t ) solves the standard heat equation v t ( x, t ) = kv xx ( x, t ) v ( x, 0) = φ ( x ) By formula, we know that v ( x, t ) = 1 4 πkt Z -∞ e - ( x - y ) 2 / 4 kt φ ( y ) dy Hence u ( x, t ) = e - bt v ( x, t ) = e - bt 4 πkt Z -∞ e - ( x - y ) 2 / 4 kt φ ( y ) dy. 18. Set w ( x, t ) = u ( x + tV, t ). By computation, if u ( x, t ) solves the heat equa- tion with convection, applying the heat operator to
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: w ( x, t ) gives w t ( x, t )-kw xx ( x, t ) = u t ( t, x ) + V u x ( x + tV, t )-ku xx ( x, t ) = 0 w ( x, 0) = u ( x, 0) = φ ( x ) . Hence w ( x, t ) = 1 √ 4 πkt Z ∞-∞ e-( x-y ) 2 / 4 kt φ ( y ) dy. However, by definition of w , u ( x, t ) = w ( x-V t, t ) and hence u ( x, t ) = w ( x-V t, t ) = 1 √ 4 πkt Z ∞-∞ e-( x-V t-y ) 2 / 4 kt φ ( y ) dy. 1...
View Full Document

This note was uploaded on 10/05/2010 for the course EE 5543 taught by Professor Sim during the Spring '10 term at Punjab Engineering College.

Ask a homework question - tutors are online